Long-Term Follow-Up and Outcomes of Autoimmune Thyroiditis in Childhood - Admoni, Osnat; Rath, Shoshana; Almagor, Tal; Elias-Assad, Ghadir; Tenenbaum-Rakover, Yardena (Frontiers in Endocrinology, 2020)
Background: Autoimmune thyroiditis (AIT) is the most common cause of acquired hypothyroidism in children. The natural outcome of AIT in childhood has been scarcely reported, with variable results. Objectives: To characterize clinical and biochemical findings at presentation of AIT, evaluate long-term outcomes and assess which parameters at presentation predict evolution over time. Study cohort: 201 children under 18 years of age at presentation (82% female) were enrolled. Subjects were divided into five subgroups according to thyroid stimulating hormone (TSH) level at referral. Results: Mean follow-up was 8.1 years (range 0–29 years). At presentation, 34% of patients had overt hypothyroidism, 32% subclinical hypothyroidism (SCH), 16% compensated hypothyroidism, 14% were euthyroid, and 3.7% had Hashitoxicosis. Children with overt hypothyroidism were younger (10.6 vs. 13.2 years) and had higher thyroid peroxidase antibody titers. At the time of the study, levothyroxine (LT4) therapy was required in 26% of children who were euthyroid at presentation, 56% of SCH patients, 83–84% of those with TSH above 10 mIU/L, and 57% of those with Hashitoxicosis. Over the years, 16% of children presenting with overt hypothyroidism stopped therapy. Free T4 at presentation was the only predictor of outcome over time. Conclusions: Our findings suggest that only 26% children who were euthyroid at presentation developed hypothyroidism, whereas over 50% of those with SCH went on to require treatment. Of those presenting with overt hypothyroidism, 16% recovered with time. The only predictive parameter for LT4 therapy at the end of the study was free T4 levels at presentation. Long-term follow-up is required to determine ongoing therapy needs and screen for additional autoimmune diseases.